Comparative Evaluation of Surgical Techniques for Pterygium Management: An In Vitro Study - Abdulmajeed Alharbi (Wolters Kluwer Medknow Publications, 2024)
Background: Pterygium is a common ocular surface disorder characterized by the growth of fibrovascular tissue onto the cornea, leading to discomfort and visual impairment. Various surgical techniques, including conjunctival autografting, amniotic membrane transplantation, and bare sclera excision, are employed in the management of pterygium. Materials and Methods: Cultured human conjunctival epithelial cells were subjected to simulated pterygium conditions, mimicking the fibrovascular proliferation observed in vivo. Subsequently, different surgical techniques, including conjunctival autografting, amniotic membrane transplantation, and bare sclera excision, were simulated in vitro. Cell viability, proliferation, migration, and inflammatory cytokine expression were assessed using various assays, including MTT assay, scratch assay, and enzyme-linked immunosorbent assay (ELISA). Untreated cells served as controls for comparison. Results: Conjunctival autografting demonstrated superior outcomes in terms of cell viability and proliferation compared to amniotic membrane transplantation and bare sclera excision. Autografted cells exhibited a significantly higher percentage of viable cells and enhanced proliferative capacity compared to cells subjected to other surgical techniques (P < 0.05). Additionally, conjunctival autografting promoted faster cell migration into the defect area, resulting in more rapid wound closure compared to other techniques. Furthermore, reduced expression of inflammatory cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), was observed in cells treated with conjunctival autografts compared to other groups. Conclusion: In vitro findings suggest that conjunctival autografting may offer superior outcomes in the management of pterygium compared to amniotic membrane transplantation and bare sclera excision.